The Power of Website and Social Media for Strengthening Brand Image, E-WoM, and Purchase Decision - Mochamad Nurhadi; Tatik Suryani; Abu Amar Fauzi (Journal of Economics, Business, and Accountancy Ventura, 2022)
Nowadays, it becomes intriguing to observe the use of websites and social media by SMEs to market their products, especially in terms of seeing customer behavior. Some previous research found the effect of social media on attitude and consumer behaviors area, but less of the focus on website and social media quality and the effect on brand awareness, brand image, E-WoM, and purchase decision and the relationship among these concepts. This research examines the effect of websites and social media from the perspective of quality dimensions on brand awareness and the influence of brand awareness, E-WoM, and brand image on purchase decisions. In addition, this study has conducted purposive sampling for the 397 respondents who had transacted through the SMEs’ website or social media in two major cities in Indonesia: Jakarta and Surabaya. The PLS-SEM analysis technique was conducted in this study. The result found that there is a positive influence of website quality and social media quality on brand awareness, as well as the influence of brand awareness on E-WoM, brand image, and purchase decisions. In addition, this study also found the influence of E-WoM and brand image on purchase decisions. The findings suggest that it is very important for SMEs to formulate a strategy for improving the quality of their website and social media to strengthen their brand awareness of consumers.